Income Convergence in Poland vis-à-vis the EU: Major Trends and Prospects - Zbigniew Matkowski; Mariusz Prochniak; Ryszard Rapacki (Poland. Competitiveness Report 2016. The Role of Economic Policy and Institutions, 2016)
The chapter intends to assess income convergence among the 11 Central and Eastern European (CEE) countries that joined the EU in 2004, 2007, and 2013: Poland, Bulgaria, Croatia, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Romania, Slovakia, and Slovenia (EU11). Convergence in these countries is analyzed in relation to the old EU members (EU15). We also present a simulative forecast of the catching-up process between the CEE countries and Western Europe. Our forecast (or, more precisely, simulation) will be made according to three hypothetical scenarios.
Keywords: O47; O52; 330; economic growth; convergence